2007
DOI: 10.1007/s11060-007-9424-1
|View full text |Cite
|
Sign up to set email alerts
|

Low HER2-expressing glioblastomas are more often secondary to anaplastic transformation of low-grade glioma

Abstract: To our best knowledge, our study showed for the first time a significant association between HER2 expression and the type of GBM, with subsequent influence on survival rate. GBM with low-HER2 expression are more likely to be secondary GBM, carrying a better prognosis than de novo GBM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 30 publications
0
62
0
6
Order By: Relevance
“…The results of ROC analysis of mean and maximum CBV and rCBV values as predictors of PFS 12 were not statistically significant when the oligodendrogliomas and oligoastrocytomas (separately and together) were included (P Ͼ .15). For astrocytomas only, the CBV max threshold of Ͼ4.2 was found to be a significant cutoff value for recurrence/progression prediction with 77.8% sensitivity and 94.4% specificity (P ϭ .0001), whereas the cutoff value of Յ3.8 was a significant predictor for 1-year survival (93.7% sensitivity, 72.7% specificity, P ϭ .0002).…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…The results of ROC analysis of mean and maximum CBV and rCBV values as predictors of PFS 12 were not statistically significant when the oligodendrogliomas and oligoastrocytomas (separately and together) were included (P Ͼ .15). For astrocytomas only, the CBV max threshold of Ͼ4.2 was found to be a significant cutoff value for recurrence/progression prediction with 77.8% sensitivity and 94.4% specificity (P ϭ .0001), whereas the cutoff value of Յ3.8 was a significant predictor for 1-year survival (93.7% sensitivity, 72.7% specificity, P ϭ .0002).…”
Section: Resultsmentioning
confidence: 91%
“…ROC analysis of the WHO grading system as a predictor of PFS 12 showed that WHO grade Ͼ2 demonstrated significant (P ϭ .0001) sensitivity (88.9%) and specificity (72.2%) in predicting recurrence (Fig 4). The predictability of 1-year survival based on the histopathologic grading was also statistically significant (sensitivity, 81.2%; specificity, 90.9%; P ϭ .0002).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…10 This receptor is well suited for this purpose because it is expressed in a considerable (15-80%) fraction of HGGs 11,12 and is a pejorative prognosis factor for several cancers including brain tumors. [13][14][15] Notably, HER2 is not expressed in adult central nervous system; 16 hence, it is a highly specific target for oncolytic virotherapy. The study was conducted in an immunodeficient mouse strain (NOD/ SCID) in order to better challenge the safety of the recombinant virus.…”
Section: Introductionmentioning
confidence: 99%